FORENSIC MEDICAL ASPECTS OF MORPHOLOGICAL DIAGNOSIS AND DETERMINATION OF THE ORIGIN OF CHRONIC SUBDURAL HEMATOMA - Tursunov Jakhongir Gulom ugli (Research Focus International Scientific Journal, 2026)
Chronic subdural hematoma is an independent progressive pathological condition of significant clinical and forensic importance. One of the most challenging tasks in forensic medical practice is the determination of the age and origin of chronic subdural hematomas, particularly in cases lacking reliable clinical information about prior traumatic brain injury. This article analyzes current concepts regarding morphological criteria for estimating the age of subdural hemorrhages, the dynamics of their organization, and the formation of encapsulated chronic hematomas. Histological features of hemorrhage resorption and organization are described in detail, including the structural characteristics of the inner and outer membranes, the role of neoangiogenesis, and recurrent microhemorrhages in the progression of chronic subdural hematoma. Special attention is given to the differential diagnosis between traumatic and non-traumatic chronic subdural hematomas from a forensic medical perspective. Practical macroscopic and microscopic criteria are proposed that may assist in presumptive determination of the hematoma’s origin. The findings presented may enhance the objectivity and evidentiary value of forensic medical conclusions.